A reporting framework for describing and a typology for categorizing and analyzing the designs of health care pay for performance schemes - Yewande Kofoworola Ogundeji; Trevor A. Sheldon; Alan Maynard (BMC, 2018)
Abstract Background Pay for Performance (P4P) has increasingly being adopted in different countries as a provider payment mechanism to improve health system performance. Evaluations of pay for performance (P4P) schemes across several countries show significant variation in effectiveness, which may be explained by differences in design. There is however no reliable framework to structure the reporting of the design or a typology to help analyse and interpret results of P4P schemes. This paper reports the development of a reporting framework and a typology of P4P schemes. Methods P4P design features were identified from literature and then explored using relevant theories from behavioural and economic science. These design features were then combined with the help of multidimensional tables to produce a reporting framework and a typology which was tested using 74 P4P studies. The inter-rater reliability of the typology was assessed using Fleiss' Kappa. Results A Healthcare Incentive Scheme Reporting Framework (HISReF) was developed consisting of nine design features. This was collapsed into a typology consisting of 4 items/design features. There was good inter-rater reliability on all the four items on the typology (kappa > 0.7). Conclusion The HISReF provides an important first step towards establishing a common language in which intervention designers can clearly specify the content of P4P designs. Our typology may be used to aid evidence synthesis and interpretation of results of P4P schemes.